Idiom-idiom Estetik Cerita Teater Tradisional Amaq Abir - Rapi (TAMUMATRA, 2024)
The traditional drama story Amaq Abir is a story performed in the traditional Amak Abir theater performance in Nyampe hamlet, Marong village. As an art form, the story highlights the local wisdom values of the Sasak tribe which is interesting to study, especially in eastern aesthetic studies. Eastern aesthetics as a study of traditional drama has not been widely studied. The aim of this research is to find the form and meaning of eastern aesthetics which are keywords in the traditional drama story Amaq Abir. The theory used is eastern aesthetics. Aesthetics can be interpreted as the beauty/truth that forms a work. Meanwhile, the method is used in this research is a qualitative method with a descriptive nature. In interpreting data, holistic methods are used. This method used in interpreting philosophical meaning. The results of the research found that there are aesthetic idioms that form the traditional drama story Amak Abir, including steadfast, explaining human character who has principles in thinking and acting. Adigang-adigung explains the arrogant and arrogant character of humans. Manut explains the human character who obeys the orders. Jiwe-seli explains the human character who cares about others/gotong royong. Sekti explains the character of humans who have extensive knowledge. Litem-putek explains the character of humans who have the characteristics of good and bad.